Immunological and oxidative stress responses of the bivalve Scrobicularia plana to distinct patterns of heatwaves. Issue 106 (November 2020) - Amorim, V.E.; Gonçalves, O.; Capela, R.; Fernández-Boo, S.; Oliveira, M.; Dolbeth, M.; Arenas, F.; Cardoso, P.G.
Abstract: As a consequence of global warming, extreme events, such as marine heatwaves (MHW), have been increasing in frequency and intensity with negative effects on aquatic organisms. This innovative study evaluated for the first time, the immunological and physiological response of the estuarine edible bivalve Scrobicularia plana to different heatwaves, with distinct duration and recovery periods. So, extensive immune (total haemocyte count - THC, haemocyte viability, phagocytosis rate, respiratory oxidative burst of haemocytes, total protein, protease activity, nitric oxide and bactericidal activity of plasma) and oxidative stress (lipid peroxidation - LPO, superoxide dismutase - SOD, catalase - CAT and glutathione-S-Transferase - GST) analyses were performed in an experimental study that tested the impact of heatwaves during 25 days. The survival and condition of S. plana were not affected by the exposure to the extreme events. However, our data suggested that longer heatwaves with shorter recovery periods can be more challenging for the species, since THC and phagocytic activity were most affected under the temperature increase conditions. Regarding the oxidative status, the species increased its SOD activity while MDA production slightly declined to the increase of temperature, protecting the organism from cellular damage. These results indicate that S. plana has a great capacity to adapt to environmental temperature changes, however, the expected higher frequency/duration of heatwaves with climate change trends can cause some debility of the species face to other stressors, which can compromise its success in the future. Graphical abstract: Image 1 Highlights: Metabolic responses of the bivalve S. plana to different heatwaves were assessed. Phagocytosis and THC were most affected under increased temperature. Face to increased temperature, SOD activity raised while MDA production declined. Longer heatwaves with shorter recovery periods can be more harmful for the species.